KESESUAIAN RUMUS DJAGRA DAN PITA UKUR TERHADAP BOBOT BADAN SAPI BALI JANTAN DI RUMAH POTONG HEWAN (RPH) KABUPATEN MERAUKE - Wisnu Barata; Henny V Saiya; A. Tenny Damayanti Indriastuti (Musamus Journal of Livestock Science, 2019)
This study aims to provide information on the suitability of measuring tape with the Djagra formula on the body weight of Bali cattle in abattoir (RPH) of Merauke Regency. This research had been conducted for 2 months, starting from August to October 2017. The methods used in this research are descriptive and direct survey on the male cattle. The parameter measured includes body weight, body length, and chest circumference on male Bali cattle. The Assessment of body weight of Bali males made using several measuring components such as measuring tape, scales and Djagra formula. Variable of measurement approaches the real weight that used the measuring tape. Based on result that the using of measuring tape has potential value closer to the real scale than the value of measurement using the Djagra formula. The Djagra formula is not suitable for measuring male Bali cattle. Keywords: Djagra formula; measuring tape; Bali cattle